2016
DOI: 10.1037/rel0000051
|View full text |Cite
|
Sign up to set email alerts
|

The spiritual development of emerging adults over the college years: A 4-year longitudinal investigation.

Abstract: Within the past decade, there has been a growing base of research literature on the developmental stage that Jeffrey Arnett ( 2004) termed emerging adulthood. While there is still much to be known about emerging adulthood in general, even less is known about the religious and spiritual lives of emerging adults. To date, few if any studies have specifically sought to explore the spiritual development of Evangelical Christian students attending an explicitly Christian college-an educational context that openly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Items were rated on a 5-point scale, ranging from 1 ( never true ) to 5 ( always true ). Past studies have found this scale to be reliable and valid (e.g., Benson et al, 1993; Hall et al, 2016). In the current study, Cronbach Alphas were acceptable (from 0.93 to 0.95) at the three time points.…”
Section: Methodsmentioning
confidence: 89%
“…Items were rated on a 5-point scale, ranging from 1 ( never true ) to 5 ( always true ). Past studies have found this scale to be reliable and valid (e.g., Benson et al, 1993; Hall et al, 2016). In the current study, Cronbach Alphas were acceptable (from 0.93 to 0.95) at the three time points.…”
Section: Methodsmentioning
confidence: 89%
“…For instance, moving out of the parental home to attend college and gaining exposure to higher educational institutions are known to have a secularizing impact on religious beliefs (Schwadel 2011; Uecker, Regnerus, and Vaaler 2007). As the social world of emerging adults change, many may begin to question or doubt their faith (Hall, Edwards, and Wang 2016; Haney and Rollock 2020; Kimball et al. 2016; Liang and Ketcham 2017; Zarzycka and Zietek 2019).…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to the goal of diminishing psychological distress in faith-based higher education, IR is operationalized in residential life and curricular settings with an awareness of the intrapersonal impact. As Hall et al (2016) found in their longitudinal research with emerging adults, spiritual growth is facilitated through engaging in relationships, developing biblical and theological perspectives, and coming to terms with suffering. These findings are helpful for offices of college student development which seek to provide optimal contexts for personal growth and identity development for all students.…”
Section: Discussionmentioning
confidence: 95%